Investigating the Impact of Corporate Governance on Financial Performance of Commercial Banks in Ghana - Yeboah, Michael; Yeboah, Benjamin; Djan, George Ohene; Ali, Mazurina Mohd; Adarkwa, Ofori Samuel (International Review of Management and Marketing, 2025)
As a popular mechanism, corporate governance is broadly recognized to align individual interests with organizational objectives, thus improving organizational performance. Nevertheless, the specific pathways through which corporate governance influences performance remain underexplored in the context of Ghanaian banks. With the data of seven listed Ghanaian banks over the period 2012 to 2022, this study examines the effect of corporate governance on bank performance, with bank size and ownership serving as moderating variables. Return on assets (ROA) is employed as a proxy for performance, while board size, board gender diversity, and the proportion of non-executive directors represent corporate governance indicators. Bank growth, interest coverage, asset tangibility, and bank size are included as control variables. Using panel data, the study applies a fixed-effects model to test the hypotheses. The findings reveal that board gender diversity exerts a significant positive effect on ROA, while board size and the proportion of non-executive directors show no significant impact at the 5% level. Moreover, neither bank size nor ownership significantly moderate the relationship between corporate governance variables and bank performance. The study suggests that banks should increase female representation on boards, while regulators such as the Bank of Ghana may place less emphasis on bank size when enforcing corporate governance practices.